(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: Thyroid hormone is a central regulator of body functions. Disorders of thyroid function are considered to be a cause of electrolyte disorders. Only few data on the association between thyroid function and electrolyte disorders exists. METHODS: In the present retrospective analysis data from all patients admitted to the Department of Emergency Medicine of a university hospital who had measurements of thyroid function (TSH, fT3, fT4) and electrolytes were included. RESULTS: 9,012 patients with measurement of TSH and electrolytes were available. 86% of patients had normal, 4% suppressed and 10% elevated TSH. Serum sodium was significantly lower in patients with high TSH levels (p <0.01). There was a significant correlation between serum TSH and phosphate level (p <0.05). Phosphate levels were higher in patients with elevated TSH than in patients with normal TSH (p <0.01). Serum calcium and magnesium correlated significantly with TSH (p <0.05). fT3 levels correlated significantly with calcium (p <0.05). Hyponatraemia was present in 14% of patients with high TSH and was significantly more common than in the group with normal TSH levels of which 9% had hyponatraemia (p <0.01). Hypokalaemia was more common in the group with elevated TSH than in those with normal TSH (14 versus 11%, p = 0.016). Hyperkalaemia was more common in the group with high TSH levels (7%) than in those with normal TSH (7 vs. 4%, p <0.01). CONCLUSION: An association between thyroid function and electrolyte disorders seems to exist, although it is probably only relevant in marked hypo-/hyperthyroidism.